Infographic. A systematic review of injuries in amateur and professional golfers - Williamson, T. R.; Duncan, J.; Kay, R. S.; Robinson, P. G.; Murray, A. D.; Clement, N. D. (British Journal of Sports Medicine, 2024)
Introduction Golf is an Olympic sport played by more than 100 million players of all ages in more than two-thirds of countries worldwide. Professional golfers have differing demographic profiles, swing mechanics (faster and increased force production) and play more than amateur golfers, so they have differing risk profiles when assessing injury epidemiology.Our systematic review and meta-analysis aimed to determine the prevalence and incidence of musculoskeletal injury in both amateur and professional golfers and to identify common injury sites and factors associated with injury.